2016
DOI: 10.1063/1.4939434
|View full text |Cite
|
Sign up to set email alerts
|

Capillarity ion concentration polarization for spontaneous biomolecular preconcentration mechanism

Abstract: Ionic hydrogel-based ion concentration polarization devices have been demonstrated as platforms to study nanoscale ion transport and to develop engineering applications, such as protein preconcentration and ionic diodes/transistors. Using a microfluidic system composed of a perm-selective hydrogel, we demonstrated a micro/nanofluidic device for the preconcentration of biological samples using a new class of ion concentration polarization mechanism called "capillarity ion concentration polarization" (CICP). Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…It affects local charge concentration and material transport. With the ICP effect, ion transport can be selectively controlled …”
Section: Introductionmentioning
confidence: 99%
“…It affects local charge concentration and material transport. With the ICP effect, ion transport can be selectively controlled …”
Section: Introductionmentioning
confidence: 99%
“…Our previous work presented the spontaneous preconcentration (or selective preconcentration) method in microfluidic chip with leveraging convective flow through microchannel over diffusiophoresis induced by imbibition and ion exchange of ion exchange medium, respectively [13][14][15][16][17][18]. Especially, we had demonstrated that the velocity of the convective flow by the imbibition of the medium deviated from original Darcy's law using non-uniformly patterned ion exchange medium, but this work has the limitation of time-consuming and complex process [13].…”
Section: Introductionmentioning
confidence: 99%
“…Label-free biosensors have various benefits; they are low-cost point-of-care diagnostic devices with high sensitivity. Therefore, we used interdigitated microelectrodes (IME) as an electrical sensing platform 32 . A two-stage approach provided a locally analyte-concentrated area for sensing, and the label-free biosensors detect the highly concentrated analytes after biomarker preconcentration.…”
Section: Introductionmentioning
confidence: 99%